2017
DOI: 10.1161/hypertensionaha.116.08791
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and Blood Pressure in 110 000 Mexican Adults

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 33 publications
(49 reference statements)
9
29
1
Order By: Relevance
“…Obesity, as well as physical inactivity during leisure, are recognized to have independent relationships with high blood pressure, and the possible interdependent relationship between these exposures in predicting high blood pressure has been reported . In the present study, we confirmed that both overweight and obesity and leisure‐time physical activity have a joint and independent relationship with high blood pressure.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Obesity, as well as physical inactivity during leisure, are recognized to have independent relationships with high blood pressure, and the possible interdependent relationship between these exposures in predicting high blood pressure has been reported . In the present study, we confirmed that both overweight and obesity and leisure‐time physical activity have a joint and independent relationship with high blood pressure.…”
Section: Discussionsupporting
confidence: 84%
“…Obesity has a clear effect on blood pressure regulation . This effect is explained by the fact that adipocytes synthesize and release several hormones (eg, adiponectin, leptin, and angiotensin) that activate the sympathetic nervous system, renin‐angiotensin‐aldosterone system, oxidative stress and systemic inflammation; leading to reductions of nitric oxide synthesis, causing endothelial dysfunction and vascular hypertrophy, which are risk factors for high blood pressure .…”
Section: Discussionmentioning
confidence: 99%
“…Differently from De Pergola et al observation that perirenal fat thickness was associated with an increase in DBP but not in SBP, in our population, we documented a significant correlation between perirenal fat and high SBP; also in the study population, perirenal fat thickness turned out to be an independent predictor of high SBP. Furthermore, the finding of a positive correlation between perirenal fat thickness and WC, a predictor of arterial hypertension, strengthens the hypothesis of its central role in hypertension development in obese subject.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, the finding of a positive correlation between perirenal fat thickness and WC, a predictor of arterial hypertension, 15,16 strengthens the hypothesis of its central role in hypertension development in obese subject.…”
Section: Ta B L E 1 Population Characteristics At Baselinesupporting
confidence: 71%
“…However, the relationship between NC and hypertension is not fully understood; some studies suggest that upper‐body subcutaneous fat might increase fatty acid release, induce insulin resistance and cause endothelial damage. On the contrary, some studies suggest that overall adiposity may be more important than central adiposity for blood pressure; suggesting that the predictors for blood pressure may be somewhat different from those for IABPD. Also, NC is highly correlated with obstructive sleep apnea syndrome, a well‐known cardiovascular risk factor .…”
Section: Discussionmentioning
confidence: 99%